Natural Rock Art designs in Balochistan: A case study of Princes of Hopes, Makran Coastal Highway - Huma, Zil e (Pakistan Languages and Humanities Review, 2024)
Balochistan’s natural rock formations, especially those seen along the Makran Coastal Highway, provide interesting new perspectives on the geological past, aesthetic appeal, and cultural importance of the area. Among these formations, the Princess of Hope, which is found in Hingol National Park, is a remarkable illustration of naturally occurring rock art that has been shaped over ages by weather and wind erosion. In order to comprehend the phenomenon of natural rock art in the area more broadly, this study looks into the Princess of Hope. The Princess of Hope is an example of how natural forces may combine artistry and geology to create structures that mimic works of human-made art, thanks to its anthropomorphic traits. This rock formation was sculpted over millions of years, mostly from sedimentary sandstone and limestone. The study also highlights how crucial it is to preserve these kinds of natural formations because they are fragile byproducts of the past that are susceptible to alterations in the environment and human interference. The Princess of Hope is a natural landmark that also adds to Balochistan’s cultural and ecological story by fusing the artistic interpretation of nature with human thought. The Princess of Hope and other natural rock art formations are priceless geological and cultural assets, and this article suggests that in order to maintain their aesthetic, ecological, and cultural significance for future generations, integrated management approaches are necessary.